EFEKTIVITAS PENAGIHAN PAJAK DENGAN SURAT TEGURAN DAN SURAT PAKSA TERHADAP PENERIMAAN PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA PONTIANAK BARAT - Arianda, Iqbal Putra (ABDI EQUATOR, 2025)
The awareness of society in paying taxes has become the responsibility of the community or taxpayers to actively participate in supporting the country's financing. In efforts to increase the state's revenue from the tax sector, the government continues to innovate. Some efforts undertaken by the Directorate General of Taxation to enhance tax revenue include implementing tax reforms. Researchers employed the method of Library Research and Field Study. The analytical method used in this research is the descriptive ratio analysis method. The ratio analyses applied include effectiveness ratios and contribution ratios. The results of the tax collection effectiveness with Reprimand letters and Forced letters at the West Pontianak Primary Tax Office have been considered ineffective over the past 3 years. The contribution of overdue tax settlement with Reprimand letters and Forced letters to tax revenue at the West Pontianak Primary Tax Office has been significantly insufficient over the past 3 years.